Germline and somatic drivers in inherited hematologic malignancies - Zoller, Julian; Trajanova, Despina; Feurstein, Simone (Frontiers in Oncology, 2023)
Inherited hematologic malignancies are linked to a heterogenous group of genes, knowledge of which is rapidly expanding using panel-based next-generation sequencing (NGS) or whole-exome/whole-genome sequencing. Importantly, the penetrance for these syndromes is incomplete, and disease development, progression or transformation has critical clinical implications. With the earlier detection of healthy carriers and sequential monitoring of these patients, clonal hematopoiesis and somatic driver variants become significant factors in determining disease transformation/progression and timing of (preemptive) hematopoietic stem cell transplant in these patients. In this review, we shed light on the detection of probable germline predisposition alleles based on diagnostic/prognostic 'somatic' NGS panels. A multi-tier approach including variant allele frequency, bi-allelic inactivation, persistence of a variant upon clinical remission and mutational burden can indicate variants with high pre-test probability. We also discuss the shared underlying biology and frequency of germline and somatic variants affecting the same gene, specifically focusing on variants in DDX41, ETV6, GATA2 and RUNX1. Germline variants in these genes are associated with a (specific) pattern or over-/underrepresentation of somatic molecular or cytogenetic alterations that may help identify the underlying germline syndrome and predict the course of disease in these individuals. This review is based on the current knowledge about somatic drivers in these four syndromes by integrating data from all published patients, thereby providing clinicians with valuable and concise information.